Thread of love - Sehgal, Kabir; Sehgal, Surishtha (Beach Lane Books, 2018)
Three siblings enjoy the Indian festival of Raksha Bandhan, a celebration of the special relationship between brothers and sisters, in this reinterpretation of the song Frère Jacques.